Effect of prednisolone on glyoxalase 1 in an inbred mouse model of aristolochic acid nephropathy using a proteomics method with fluorogenic derivatization-liquid chromatography-tandem mass spectrometry. - Shih-Ming Chen (PLoS ONE, 2020)
Prednisolone is involved in glucose homeostasis and has been used for treatment for aristolochic acid (AA) nephropathy (AAN), but its effect on glycolysis in kidney has not yet been clarified. This study aims to investigate the effect in terms of altered proteins after prednisolone treatment in a mice model of AAN using a proteomics technique. The six-week C3H/He female mice were administrated AA (0.5 mg/kg/day) for 56 days. AA+P group mice were then given prednisolone (2 mg/kg/day) via oral gavage for the next 14 days, and AA group mice were fed water instead. The tubulointerstitial damage was improved after prednisolone treatment comparing to that of AA group. Kidney homogenates were harvested to perform the proteomics analysis with fluorogenic derivatization-liquid chromatography-tandem mass spectrometry method (FD-LC-MS/MS). On the other hand, urinary methylglyoxal and D-lactate levels were determined by high performance liquid chromatography with fluorescence detection. There were 47 altered peaks and 39 corresponding proteins on day 14 among the groups, and the glycolysis-related proteins, especially glyoxalase 1 (GLO1), fructose-bisphosphate aldolase B (aldolase B), and triosephosphate isomerase (TPI), decreased in the AA+P group. Meanwhile, prednisolone decreased the urinary amount of methylglyoxal (AA+P: 2.004 ± 0.301 μg vs. AA: 2.741 ± 0.630 μg, p < 0.05), which was accompanied with decrease in urinary amount of D-lactate (AA+P: 54.07 ± 5.45 μmol vs. AA: 86.09 ± 8.44 μmol, p < 0.05). Prednisolone thus alleviated inflammation and interstitial renal fibrosis. The renal protective mechanism might be associated with down-regulation of GLO1 via reducing the contents of methylglyoxal derived from glycolysis. With the aid of proteomics analysis and the determination of methylglyoxal and its metabolite-D-lactate, we have demonstrated for the first time the biochemical efficacy of prednisolone, and urinary methylglyoxal and its metabolite-D-lactate might be potential biomarkers for AAN.